MSME accounting workshop for students at the Kafalatul Yatama Orphanage, Ngaliyan, Semarang - Muhammad Ihlashul Amal; Asrori Asrori; Fachrurrozie Fachrurrozie; Indah Fajarini Sri Wahyuningrum; Prabowo Yudo Jayanto; Fian Tri Rohmah (Universitas Muhammadiyah Magelang, 2022)
The students of the Kafalatul Yatama Orphanage are the next generation of the nation who have the same rights in getting protection, love and adequate education for their future. The focus of this service is education on small and medium micro accounting and social development. In particular, the purpose of this community service is to provide MSME accounting knowledge and simple bookkeeping skills to orphanage students so that they are able to compile financial reports such as statements of financial position, profit and loss, and cash flow when they carry out entrepreneurial activities. Service activities are carried out using a training method consisting of 3 stages, namely, preparation, implementation, and evaluation. The results achieved from this activity are delivering knowledge and ability to book and prepare MSME financial reports.